Chiral Exciplex Acceptor Enables Circularly Polarized Electroluminescence with High Dissymmetry Factor Close to 10−2. Issue 23 (18th September 2022) - Gu, Qing; Chen, Zijian; Xie, Wentao; Qiu, Weidong; Peng, Xiaomei; Jiao, Yihang; Li, Mengke; Liu, Zhe; Sun, Guanwei; Lu, Yanfei; Gan, Yiyang; Liu, Kunkun; et al.
Abstract: Chirality is a magical property that exists in nature universally, ranging from the spin of microscopic electrons to the galaxies. Furthermore, circularly polarized organic electroluminescent materials have promising prospects in improving the brightness of displays, but there are still some problems. At present, most of chiral thermally activated delayed fluorescence small molecules show relatively low circularly polarized luminescence (CPL) dissymmetry factors between 10 −4 and 10 −3 because of the electric dipole‐allowed but magnetic dipole‐forbidden transition of the singlet state. In this work, a promising strategy is reported for constructing chiral exciplex systems with a chiral electron acceptor and a regular achiral donor to achieve high CPL dissymmetry factors in both photoluminescence and electroluminescence. From theoretical calculation results, the exciplex systems possess a large separation of the highest occupied molecular orbital and the lowest unoccupied molecular orbital in donor and acceptor molecules, respectively, which results in comparable electric and magnetic transition dipole moments. The resultant CPL organic light‐emitting diodes based on the exciplex systems as emitters show low turn‐on voltage of 2.4 V, high external quantum efficiencies of 12.7% and 9.3%, and opposite circularly polarized electroluminescence with high dissymmetry factors ( g EL ) of +7.25 × 10 −3 and −9.89 × 10 −3 . Abstract : The exciplex system, containing a novel acceptor S‐TRZ and commercially available hole transport material TAPC as the donor, shows good photophysical properties and excellent chiroptical property with | g EL | of 9.89 × 10 −3, which is the highest value among the circularly polarized organic electroluminescent devices by the perturbation strategy so far.